Comparação da capacidade de formulações medicamentosas de diferentes quimioterápicos em induzir morte celular em células da linhagem MB49 de tumor de bexiga murino - Trevisoli, Pablo Gil Mortol (Universidade Federal de São Carlos, 2018)
Despite recent advances in cancer prevention and treatment, bladder urothelial carcinoma continues to be one of the most common types of malignant neoplasms in the world, with a 20% mortality rate. The cells and molecules of the immune system are fundamental components of the tumor microenvironment. Probably the fact that the neoplastic cell shares antigens with normal cells, have high growth rate and suffer edition, contributes to its resistance to the antitumor immune response. Even with these obstacles, the immune response remains one of the best bets in the malignant neoplasms treatment. In the past, homeostatic cell death, which often occurs through apoptosis, was irrelevant to the antitumor immune response since it was unable to stimulate the immune system. However, in recent years, it has been observed that certain types of apoptosis were able to induce immune response against dead cell antigens, particularly when they were derived from malignant neoplasms. This type of phenomenon was called immunogenic cell death (ICD). Despite advances in the discovery of the mechanisms involved in cell death associated with various tumor lines, no work to date has evaluated its efficacy in the model of bladder cancer induced by chemotherapeutics commonly used in the treatment of this disease.Therefore, the aim of the present study was to evaluate the action of cisplatin, mitoxantrone, daunorubicin, doxorubicin and epirubicin on the viability of MB49 lineage cellsand to identify the best dose with apoptotic activity of cisplatin, mitoxantrone, daunorubicin and doxorubicin. The results showed that chemotherapeutics agents, in their pharmaceutical formulation, performed well against MB49 cells in vitro. Cisplatin and mitoxantrone proved to be efficient in producing apoptosis, but only in vivo tests could confirm their immunogenic effect on these cells. In addition, this work showed that the effects of viability may be quite divergent depending on the dose and time evaluated and the need for a follow-up of viability after treatment withdrawal. In addition, this work showed that the effects of viability might be quite divergent depending on the dose and time evaluated and the need to observe viability after treatment withdrawal. It is concluded that the drug formulations of daunorubicin, epirubicin, doxorubicin and mitoxantrone produced varying degrees of apoptotic death in vitro, depending on exposure time and drug concentration.
Keywords: Câncer de Bexiga; Apoptose; Cisplatina; Mitoxantrona; Daunorrubicina; Doxorrubicina; Epirrubicina; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::IMUNOLOGIA; CIENCIAS DA SAUDE